Contribution to Natural Rubber Production without Exogenous Hormonal Stimulation: An Experimental Study - Obouayeba Samuel; Diarrassouba Moussa; Konan Djézou; Obouayeba Abba Pacôme; Soumahin Eric Francis; Koffi Antoine; Adou Bini Christophe; Ballo Espérance Kouadio (Current Topics in Agricultural Sciences Vol. 6, 2022)
The stimulation of the latex-producing metabolism is critically necessary for rubber production and, more importantly, its growth. Can the rubber tree’s latex-producing metabolism activation process lead to increased yield without the need of exogenous hormones? To verify this decisive hypothesis, many works, were conducted for nine years in Southern Côte d’Ivoire, were conducted on some 15 clones (IRCA 18, IRCA 209, IRCA 111, IRCA 130, PB 235, PB 260, PB 280, PB 330, PB 310; GT 1, BPM 24, RRIC 100; PB 217 and PR 107) of the three metabolisms respectively, active, moderate and slow, with two main statistical designs. On a small scale, in a “one-tree plot” design, the same latex harvesting system, tapping in d4 with distinct hormonal stimulation regimes (0/y; 2/y; 4/y; 6/y; 8/y; 13/y; 18/y; 26/y, 39/y and 78/y), has been applied to all treatments. In a randomized complete block design, verious tapping frequencies (d2, d3, d4, d5 and d6) and hormonal stimulation (0/y, 4/y, 8/y and 10/y) were employed . Whatever the stimulation regime, the mean g.t-1.t-1 of the unstimulated control (56) of the active metabolism clones (PB 235, PB 310, IRCA 111 and IRCA 130) more than 9 years was done statistically the same order that of the stimulated patterns (54). The average g.t-1.t-1 of the control (60) was less than that of the greatest yielding stimulated patterns (67) of the clones (PB 330, PB 280, PB 260, IRCA 18 and IRCA 209). The Mean g.t-1.t-1of the unstimulated control (49) was significantly below than that of the greatest yielding stimulated treatment (57) of moderate metabolism clones (GT 1, BPM 24 and RRIC 100). The Mean g.t-1.t-1 of the unstimulated control (39) was significantly below than that of the most yielding stimulated treatment (70) of slow metabolism clones (PB 217 and PR 107). On a large scale and at tapping frequency (d2), the unstimulated latex harvesting system (d2 0/y) revealed an average outcome of (2341; 2266 and 1849 kg.ha-1.year-1 for the active, moderate and slow metabolisms, respectively) statistically comparable to those of the greatest yielding tapping frequencies d3, d4, d5 and d6 all latex harvesting systems combined for the clones studied (2388; 2348 and 2256 kg.ha- 1.year-1). These findings reveal that by strategically manipulating tapping intensity, natural rubber can be produced without the use of exogenous hormone stimulation.